Challenges faced and lessons learned: a multi-component prospective memory training program for Malaysian older adults - Ibrahim, Rahimah; Basri, Hamidon; Madon, Zainal; Farzin, Azin (Academia Brasileira de Neurologia, 2018)
The surrounding circumstances and environments of Malaysian older adults could make conducting interventions (mainly in terms of clinical or randomized controlled trials) a challenge. Working with older adults and facing cultural issues could be challenging. Objective: This paper illustrates a significant perspective of some of the challenges faced while conducting a randomized controlled trial exploring the impact of a multi-component intervention that included strategy- and process-based prospective memory (PM) training among Malaysian older adults. Methods: The current study was a randomized controlled trial (RCT) and therefore the challenges were presented in accordance with the CONSORT statement style. Results: A discussion on how these issues were addressed is provided. Conclusion: Some suggestions were presented to help researchers plan and create interventions for similar studies and to support a practical method of addressing all related challenges.